Growth, recruitment and mortality of Pandalus borealis (Krøyer), in Balsefjord, Northern Norway - Thomassen, Tore (ICES, 1976)
A population study of the deep sea prawn started in autumn 1975. Eight months were sampled until July 1976. The von Bertalanffy growth parameters were estimated from mean carapace length of certain year classes, excluding the oldest. Values for L and K show faster growth but smaller asymtotic length compared to Barents Sea values. The maternal generation did not moult until 1.5 months after the eggs had hatched. Recruitment to the utilized stock was estimated to take place at age 1.2 years. From then instantaneous rate of mortality Z, were found to increase throughout the prawns life. This can partly be explained by an increasing ratio of predation by cod.